Edukasi Kesehatan Mental dan Pelatihan Pemanfaatan Kertas Bekas Antinyamuk Sebagai Aromaterapi pada Ibu dan Anak di Kelurahan Siantan Hilir, Kecamatan Pontianak Utara: Education on the Importance of Mother and Child Mental Health and Training on the Utilization of Used Mosquito Repellent Paper as Aromatherapy - Andhi Fahrurroji; Devia Valenstya; Lifia Putri Andini; Bulan Maharani Kusnadie; Alfian Nur Huda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
According to the World Health Organization, mental health is a state of well-being in which a person can realize their abilities, cope with the everyday stresses of life, work productively and contribute to their community. Good mental health enables people to fulfill their potential, cope with the everyday stresses of life, work productively and contribute to their communities, where it is estimated that one in four people will suffer from a mental disorder in their lifetime. Therefore, education was carried out regarding the importance of a mother's and child's mental health in the Siantan Hilir Village. The aim is to increase public knowledge and awareness regarding mental health in the Siantan Hilir Village. The method used in this research is giving interventions, implementing activities, and conducting training. The results of the activities were an increase in mothers' knowledge from 20% to 68% who understood mental health. This activity concludes that there is an increase in public knowledge about mental health, and the community becomes more aware of how to deal with stress or mental health disorders they experience.